Dynamic non Performing Loan in Indonesia (Empirical Study on Commercial and Islamic Banks) - Budi Kramadibrata; Darlin Aulia; Rizal Kamsurya; Andi Heru Susanto (Lembaga Intelektual Muda (LIM) Maluku, 2021)
This paper discusses non-performing loans in Islamic and commercial banking. This study tries to test internal and external factors such as CAR (capital adequacy ratio), interest rate, ROE (return on equity), inflation rate, and GDP (gross domestic productÂ) against non-performing loans or NPL in Indonesia banking. It would also like to see the impact of the crisis that occurred during the period 2015 to 2020. A sample from this study consisted of 66 Banks. Results showed that of the four variables tested showed a significant influence on the NPL of commercial and Islamic banks, except on the testing of inflation and CAR variables on commercial banks that showed results did not affect the NPL.